(untitled) (Journal of Fiber Bioengineering and Informatics, 2016)
Clothing can provide safety and comfort for persons exposed to both cold and hot thermal environments. To assess the potential impact of clothing moisture and wetness on fabric cooling, a series of wind-tunnel tests was conducted to quantify the evaporative cooling capacity of selected fabric samples. Single- layer cotton, polyester, nylon and silk were evaluated. The results showed that onset and magnitude of evaporative cooling was determined by the amount of water contained in a fabric sample. The results also showed that an exposed “skin” exhibited more cooling when covered with a fabric than when it was not. The information obtained helps better understand the evaporative cooling process for fabrics and assist in the selection of garment materials that optimize worker comfort and safety.